Comparative risk of cancer associated with SGLT inhibitors and DPP-4 inhibitors in patients with diabetes: a systematic review and meta-analysis - Hamed Hajishah; Parsa Mazloom; Amirhossein Salehi; Danial Kazemi; Reza Samiee; Hossein Majlesi; Mohammad Javad Amini; Arefeh Meyari; Negin Safari Dehnavi; Masood Zangi (Diabetology & Metabolic Syndrome)
Abstract Aims This systematic review and meta-analysis aimed to compare the overall and site-specific cancer risk associated with SGLT2i versus DPP4i in patients with type 2 diabetes mellitus. Methods We systematically searched PubMed, Scopus, and Web of Science for cohort studies comparing cancer incidence in adult type 2 diabetes patients treated with SGLT2i versus DPP4i. Risk ratios (RRs) with 95% confidence intervals (CIs) were pooled using a random-effects model due to significant heterogeneity (I²). Subgroup analyses by cancer type and publication bias assessment were performed. Results Seventeen cohort studies met the inclusion criteria. Overall, SGLT2i use was associated with a significantly lower risk of incident cancer compared to DPP4i use (Pooled RR = 0.77, 95%CI:0.70–0.84; I²=81.6%). Subgroup analyses revealed significantly lower risks for liver (RR = 0.76), lung (RR = 0.87), and prostate (RR = 0.75) cancers with SGLT2i. Trends towards lower risk were observed for colorectal (RR = 0.80) and stomach (RR = 0.69) cancers. No significant differences were found for bladder, breast, or pancreatic cancer risk. Conclusion This meta-analysis suggests that SGLT2 inhibitors are associated with a reduced overall risk of cancer compared to DPP-4 inhibitors in patients with type 2 diabetes mellitus, particularly for liver, lung, and prostate cancers. However, these findings are based on observational data with significant heterogeneity and varying follow-up times, requiring additional long-term research to confirm.